Multi-source retired lithium ion battery negative electrode graphite performance normalization regeneration method

A flash discharge treatment method for recycling negative electrode graphite from multiple sources effectively addresses the limitations of existing methods by regenerating damaged graphite structures and removing impurities, achieving high-performance and cost-effective regeneration.

CN119218988AActive Publication Date: 2024-12-31TSINGHUA UNIVERSITY

Patent Information

Application Number
CN202411202854.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2024-12-31
Estimated Expiration
2044-08-29

AI Technical Summary

Technical Problem

Existing recycling methods for negative electrode graphite in retired lithium-ion batteries face challenges in handling diverse waste graphite types, have poor remediation effects, high costs, and complex processes, failing to address the structural damage and impurities effectively.

Method used

A method involving mixing multiple sources of retired lithium-ion battery negative electrode graphite raw materials, followed by flash discharge treatment to regenerate graphite, utilizing controlled temperature, time, and atmosphere to repair damaged structures and remove impurities.

Benefits of technology

The method achieves efficient regeneration of graphite with improved performance, adaptability to various raw materials, low cost, and simple process, resulting in high-quality regenerated graphite with enhanced capacity and cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119218988A_ABST
    Figure CN119218988A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, in particular to a performance normalization regeneration method for negative electrode graphite of a multi-source retired lithium ion battery. The regeneration method comprises the following steps: mixing a multi-source decommissioned lithium ion battery negative electrode graphite raw material according to a certain proportion to obtain a multi-source mixed invalid graphite raw material; and adding the obtained multi-source mixed invalid graphite raw material into a graphite device, and carrying out flash discharge treatment to obtain regenerated graphite. The performance normalization regeneration method for the negative electrode graphite of the multi-source retired lithium ion battery is high in adaptability to raw materials, and can be used for repairing common retired negative electrode graphite materials in the market. According to the regeneration method, re-graphitization of the decommissioned negative electrode graphite is achieved through the flash discharge technology, the technological process is short, economical and environmentally friendly, needed equipment is simple, cost is extremely low, and the regeneration method has very high application value and remarkable economic benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a method for normalizing the performance of negative electrode graphite of multi-source retired lithium ion batteries. Background Art

[0002] As people pay more and more attention to achieving carbon neutrality, electric vehicles and energy storage facilities are developing rapidly, resulting in a surge in demand for lithium-ion batteries. However, lithium-ion batteries only have a lifespan of 3-8 years, and more than 2 million tons of lithium-ion batteries are retired each year. At present, less than 6% of retired lithium-ion batteries are recycled worldwide, and most retired lithium-ion batteries end up in landfills. However, waste batteries contain a large amount of valuable metals and strategic mineral graphite resources, and arbitrary disposal will cause a large amount of resource waste. At the same time, retired lithium-ion batteries contain a large amount of organic compounds such as electrolytes and binders. If not properly handled, they will seriously pollute the environment. Therefore, recycling retired lithium-ion batteries is an optimal choice that is environmentally friendly and in line with the sustainable development strategy.

[0003] Existing recycling methods, such as high-temperature pyrometallurgy and hydrometallurgy, mainly focus on recovering valuable metals from retired positive electrode materials, while ignoring retired negative electrode material graphite. In pyrometallurgy, graphite is burned on-site as a reducing agent to reduce the valence state of transition metals, thereby keeping the low-valence metal elements stable in solution; while in traditional hydrometallurgical methods, waste graphite is often retained in the leached slag. In addition, with the advancement of disassembly technology, the purity of retired battery materials has been significantly improved. As the main development direction in the future, the regeneration and repair of negative electrode graphite in retired battery materials deserves attention; finally, with the large-scale production of lithium-ion batteries, more and more scraps are generated in the non-standard production process, and the recycling of this part of graphite is also worthy of attention.

[0004] Given the differences in sources, production processes and separation methods, the reuse of waste graphite faces great challenges, which makes it difficult to achieve a unified regeneration process. The failure mechanism of graphite negative electrode materials involves the failure of solid electrolyte membrane (SEI), lithium dendrite growth, destruction of graphite interlayer spacing caused by solvent intercalation, and particle cracking. Although the traditional pickling process can effectively remove organic lithium-containing impurities on the surface, it will also cause varying degrees of damage to the graphite crystal structure; although the high-temperature roasting process can achieve graphitization and reconstruction of damaged graphite structures, the high cost caused by large amounts of energy consumption and the stringent requirements for equipment limit its further application; carbon coating technology can enhance the surface properties of graphite, but there are still challenges such as long processes, precise control requirements, and high costs.

[0005] Therefore, the existing technology for remediating retired negative electrode graphite is not only difficult to handle a variety of waste graphite, but also has disadvantages such as poor remediation effect, high remediation cost, and complex remediation process. It is urgent to develop a new economical recovery process for retired negative electrode graphite to achieve the normalized remediation and regeneration of retired graphite. Summary of the invention

[0006] The present invention provides a method for normalizing the performance of negative electrode graphite of multi-source retired lithium-ion batteries, which is used to solve the problems that the existing retired negative electrode graphite repair technology is not only difficult to handle a variety of waste graphites, but also has poor repair effect, high repair cost, and complicated repair process.

[0007] According to a first aspect of the present invention, the present invention provides a method for normalizing the performance of negative electrode graphite of multi-source retired lithium-ion batteries, comprising the following steps: Step 1: Mixing multiple sources of retired lithium-ion battery negative electrode graphite raw materials in a certain proportion to obtain multiple source mixed failed graphite raw materials; Step 2: Add the multi-source mixed spent graphite raw material obtained in step 1 into a graphite device, and then perform flash discharge treatment to obtain regenerated graphite.

[0008] In the above scheme, the performance normalization regeneration method of the negative electrode graphite of a multi-source retired lithium-ion battery of the present invention can effectively act on the damaged graphite structure in a short time through the Joule heat generated by flash discharge, and remove surface impurities at the same time, so as to achieve the performance normalization repair of multi-source graphite. The regeneration method of the present invention has strong adaptability to raw materials, can repair different types of retired negative electrode graphite materials on the market, can process multiple types of waste graphite at the same time, and has good repair effect, simple equipment, extremely low cost, simple repair process, and has strong application value.

[0009] The retired lithium-ion battery negative electrode graphite material in the present invention refers to the main component of the negative electrode material of the used lithium-ion battery, the failed graphite negative electrode material caused by factors such as failure of the solid electrolyte membrane, lithium dendrite growth, destruction of the graphite interlayer spacing caused by solvent intercalation, and particle cracking during use, as well as one or more of the scraps of negative electrode graphite material caused by improper cutting process and injection process during production.

[0010] Furthermore, the multi-source retired lithium-ion battery negative electrode graphite raw materials include multiple types of graphite scraps generated in the production process of negative electrode materials, negative electrode graphite materials obtained by disassembling retired power batteries, and leached slag obtained by hydrometallurgy of crushed black powder of retired power batteries.

[0011] Preferably, in the multi-source retired lithium-ion battery negative electrode graphite raw materials, the weight ratio of graphite scraps generated in the production process of negative electrode materials, negative electrode graphite materials obtained by disassembling retired power batteries, and leached slag obtained by hydrometallurgy of crushed black powder of retired power batteries is (1-5): (1-2): (1-3).

[0012] Optionally, the weight ratio of the graphite scraps produced in the production process of the negative electrode material, the negative electrode graphite material obtained by disassembling retired power batteries, and the leached slag obtained by hydrometallurgy of crushed black powder of retired power batteries can be 1:1:1, 2:1:1, 3:1:1, 4:1:1, 5:1:1, 1:1:2, 1:1:3, 2:1:2, 2:1:3, 1:2:1, 1:2:2, 1:2:3 or 5:2:2, etc., and of course it is not limited to these ratios. The difficulty of regenerating the leached slag obtained by hydrometallurgy of crushed black powder of retired power batteries is higher than that of the graphite scraps produced in the production process of the negative electrode material and the negative electrode graphite material obtained by disassembling retired power batteries. In order to achieve a better regeneration effect, it is preferred that the leached slag obtained by hydrometallurgy of crushed black powder of retired power batteries accounts for less than 50% of the weight percentage of the negative electrode graphite raw materials of multi-source retired lithium-ion batteries, preferably less than or equal to 35%. In some specific embodiments, the leached slag obtained by hydrometallurgical crushing of black powder of retired power batteries accounts for 30-35% by weight of the negative electrode graphite raw materials of multi-source retired lithium-ion batteries, which can achieve a better regeneration effect.

[0013] Furthermore, in the step 2, the flash discharge treatment is to place a graphite device containing multi-source mixed spent graphite raw materials in a flash discharge device, raise the temperature to the reaction temperature at a certain heating rate, keep the temperature for a period of time and then cool it to obtain regenerated graphite.

[0014] Furthermore, the reaction temperature is 2800-3200° C., and the insulation time is 0.1s-10s.

[0015] Optionally, the reaction temperature can be 2800°C, 2850°C, 2900°C, 2950°C, 3000°C, 3050°C, 3100°C, 3150°C or 3200°C, etc., and of course it can be other values ​​within the above range, which are not limited here. The insulation time can be 0.1s, 1s, 2s, 3s, 4s, 5s, 6s, 7s, 8s, 9s or 10s, etc., and of course it can be other values ​​within the above range, which are not limited here, preferably 0.5s-5s, more preferably 0.5s-1.5s. If the insulation time is too high, it will cause serious damage to the equipment.

[0016] In the above scheme, by limiting the reaction temperature and the insulation time within a reasonable range, it is beneficial to improve the graphitization efficiency of the raw material, thereby improving the product quality of the regenerated graphite.

[0017] Furthermore, the heating rate is 0.01°C / s to 3000°C / s, preferably 1°C / s to 3000°C / s.

[0018] Optionally, the heating rate can be 0.01℃ / s, 0.05℃ / s, 1℃ / s, 10℃ / s, 50℃ / s, 100℃ / s, 200℃ / s, 500℃ / s, 800℃ / s, 1000℃ / s, 1500℃ / s, 2000℃ / s, 2500℃ / s or 3000℃ / s, etc., and of course it can also be other values ​​within the above range, which is not limited here, and is preferably 1℃ / s to 3000℃ / s.

[0019] In the above scheme, by limiting the heating rate within a reasonable range, it is helpful to improve the graphitization efficiency of the raw material, thereby improving the product quality of the regenerated graphite.

[0020] Furthermore, the discharge current of the flash discharge treatment is 5-15A, and the discharge voltage is 150-200V.

[0021] Optionally, the discharge current of the flash discharge treatment can be 5A, 6A, 7A, 8A, 9A, 10A, 11A, 12A, 13A, 14A or 15A, etc., and of course it can also be other values ​​within the above range, which is not limited here, and is preferably 8-12A. The discharge voltage can be 150V, 160V, 170V, 180V, 190V or 200V, etc., and of course it can also be other values ​​within the above range, which is not limited here, and is preferably 170-190V.

[0022] In the above scheme, the flash discharge efficiency can be improved by limiting the discharge current and discharge voltage of the flash discharge process within a reasonable range.

[0023] Furthermore, the cooling includes natural air drying cooling or cooling at a cooling rate of 0.01°C / s to 3000°C / s. Furthermore, natural air drying cooling is prone to structural collapse. In order to maintain the original structure after graphitization to a large extent, it is preferably cooled at a cooling rate of 0.01°C / s to 3000°C / s.

[0024] Optionally, the cooling rate can be 0.01℃ / s, 0.05℃ / s, 1℃ / s, 10℃ / s, 50℃ / s, 100℃ / s, 200℃ / s, 500℃ / s, 800℃ / s, 1000℃ / s, 1500℃ / s, 2000℃ / s, 2500℃ / s or 3000℃ / s, etc., and of course it can also be other values ​​within the above range, which is not limited here, and is preferably 1℃ / s to 3000℃ / s.

[0025] Furthermore, the flash discharge treatment is performed in a specific gas atmosphere, and the specific gas includes one or more of nitrogen, argon, oxygen and air, preferably one or two of nitrogen and argon.

[0026] Furthermore, the graphite device is one or more of a graphite boat, a graphite tube and graphite carbon paper.

[0027] Furthermore, in step 2, a flash discharge treatment is performed to obtain a reaction product, and the obtained reaction product is washed and then vacuum dried to obtain regenerated graphite; Preferably, the washing solution used in the washing is a mixture of one or more of hydrochloric acid, sulfuric acid, phosphoric acid and water; more preferably, the concentration of the washing solution is 0.01 mol / L to 8 mol / L.

[0028] Some oxides produced during the graphitization process can be removed by acid washing to ensure the purity of the regenerated graphite. Optionally, the concentration of the washing solution can be 0.01 mol / L, 0.05 mol / L, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, 6 mol / L, 7 mol / L or 8 mol / L, etc., and of course it can also be other values ​​within the above range, which is not limited here.

[0029] Furthermore, in the step 1, multiple sources of retired lithium-ion battery negative electrode graphite raw materials are mixed in a certain proportion and then sieved through a 50-200 mesh sieve to obtain multiple source mixed failed graphite raw materials.

[0030] In the above scheme, the quality of the regenerated graphite is improved by removing visible plastic impurities, collector debris, etc. through screening.

[0031] Furthermore, the regenerated graphite has a gram capacity of 300 mAh / g to 400 mAh / g under 0.1C current conditions and a specific surface area of ​​2 m 2 / g~20m 2 / g, pore volume 10m 3 / g~100m 3 / g.

[0032] The invention provides a normalized regeneration method for the performance of multi-source retired lithium-ion battery negative electrode graphite, which has strong adaptability to raw materials and can repair different types of retired negative electrode graphite materials on the market. The regeneration method of the invention realizes the re-graphitization of retired negative electrode graphite through the flash discharge technology, has a short process flow, is economical and environmentally friendly, requires simple equipment, has extremely low cost, and has strong application value and significant economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0034] Figure 1 This is a schematic diagram of the process flow of a method for normalizing the performance of negative electrode graphite of multi-source retired lithium-ion batteries according to Example 1 of the present invention.

[0035] Figure 2 This is a rate performance diagram of the recycled graphite (FG) obtained in Example 1 of the present invention and several other materials (graphite scraps SG, negative electrode graphite materials DG obtained by disassembling retired power batteries, and graphite HG in hydrometallurgical leaching slag of crushed black powder from retired power batteries) under current conditions of 0.1C / 0.2C / 0.5C / 1C / 2C / 0.1C.

[0036] Figure 3 This is the first charge and discharge performance graph of the recycled graphite (FG) obtained in Example 1 of the present invention and several other materials (graphite scraps SG, negative electrode graphite materials DG obtained by disassembling retired power batteries, and graphite HG in hydrometallurgical leaching slag of crushed black powder from retired power batteries) under 0.1C current conditions.

[0037] Figure 4 This is a cycle performance diagram of the regenerated (FG) obtained in Example 1 of the present invention and several other materials (graphite scraps SG, negative electrode graphite materials DG obtained by disassembling retired power batteries, and graphite HG in hydrometallurgical leaching slag of crushed black powder from retired power batteries) after 500 cycles under 1C current conditions. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] The beneficial effects of the present invention will be described below in conjunction with specific embodiments and comparative examples.

[0040] In the following examples, the graphite scraps generated in the production process of the negative electrode materials, the negative electrode graphite materials obtained by disassembling retired power batteries, and the leached slag obtained by hydrometallurgy of crushed black powder of retired power batteries are respectively sourced from Shenzhen Xinmao New Energy Technology Co., Ltd., China New Aviation Technology Group Co., Ltd. (CALB), and Zhejiang Huayou Cobalt Co., Ltd.

[0041] Example 1

[0042] This embodiment provides a method for normalizing the performance of negative electrode graphite of multi-source retired lithium-ion batteries. The process flow diagram is as follows: Figure 1 As shown, it includes the following steps: Step 1: Mix the graphite scraps generated in the production process of the negative electrode material, the negative electrode graphite materials obtained by disassembling retired power batteries, and the leached slag obtained by hydrometallurgy of crushed black powder of retired power batteries in a ratio of 1:1:1, and sieve through a 200-mesh sieve to obtain the sieved material as the multi-source mixed spent graphite raw material.

[0043] Step 2: Take 1g of the multi-source mixed failed graphite raw material obtained in step 1 and add it to a graphite tube, place it in a flash discharge equipment heating furnace under nitrogen protection (the flash discharge equipment discharge current is 10A and the discharge voltage is 180V), heat it to 3000℃ at a heating rate of 3000℃ / s, keep it warm for 1s, cool it to room temperature at a cooling rate of 1000℃ / s and take it out. First wash it with 0.1M dilute hydrochloric acid, then wash it with deionized water until the washing liquid is neutral, and then dry it at 25℃ and -0.085MPa vacuum to obtain regenerated graphite.

[0044] Example 2

[0045] This embodiment provides a method for normalizing the performance of negative electrode graphite of multi-source retired lithium-ion batteries. The difference from Example 1 is that in step 1, the graphite scraps generated in the production process of the negative electrode material, the negative electrode graphite material obtained by disassembling retired power batteries, and the leached slag obtained by hydrometallurgy of crushed black powder of retired power batteries are mixed in a ratio of 2:1:3.

[0046] Example 3

[0047] This embodiment provides a method for normalizing the performance of negative electrode graphite of multi-source retired lithium-ion batteries. The difference from Example 1 is that in step 1, the graphite scraps generated in the production process of the negative electrode material, the negative electrode graphite material obtained by disassembling retired power batteries, and the leached slag obtained by hydrometallurgy of crushed black powder of retired power batteries are mixed in a ratio of 5:2:2.

[0048] Example 4

[0049] This embodiment provides a method for normalizing the performance of negative electrode graphite of multi-source retired lithium-ion batteries. The difference from Embodiment 1 is that the insulation time in step 2 is 5s.

[0050] Example 5

[0051] This embodiment provides a method for normalizing the performance of negative electrode graphite of multi-source retired lithium-ion batteries. The difference from Embodiment 1 is that the insulation time in step 2 is 10 seconds.

[0052] Example 6

[0053] This embodiment provides a method for normalizing the performance of negative electrode graphite of retired lithium-ion batteries from multiple sources, which is different from Embodiment 1 in that the cooling in step 2 is natural air drying cooling.

[0054] Example 7

[0055] This embodiment provides a method for normalizing the performance of negative electrode graphite of retired lithium-ion batteries from multiple sources. The difference from Embodiment 1 is that the gas atmosphere for flash discharge treatment in step 2 uses argon instead of nitrogen.

[0056] Example 8

[0057] This embodiment provides a method for normalizing the performance of negative electrode graphite of multi-source retired lithium-ion batteries. The difference from Embodiment 1 is that the gas atmosphere for flash discharge treatment in step 2 uses air instead of nitrogen.

[0058] Example 9

[0059] This embodiment provides a method for normalizing the performance of negative electrode graphite of multi-source retired lithium-ion batteries. The difference from Embodiment 1 is that in step 1, the negative electrode graphite is screened through a 50-mesh sieve.

[0060] Comparative Example 1

[0061] This comparative example provides a method for regenerating negative electrode graphite of multi-source retired lithium-ion batteries, which is different from Example 1 in that: in step 2, other methods are used to treat multi-source mixed failed graphite raw materials, and the specific treatment method is to use microwave heating to treat graphite using the wave absorption of carbon materials. Microwave heating is 800W for 5s.

[0062] Comparative Example 2

[0063] This comparative example provides a method for regenerating negative electrode graphite of multi-source retired lithium-ion batteries, which is different from Example 1 in that: in step 2, other methods are used to perform high-temperature sulfuric acid roasting on the crushed black powder hydrometallurgical leaching slag of retired power batteries. The specific treatment method is to add sulfuric acid during the roasting process for acidification treatment to achieve the removal of impurities and the reconstruction of graphite structural materials.

[0064] Comparative Example 3

[0065] This embodiment provides a method for normalizing the performance of negative electrode graphite of multi-source retired lithium-ion batteries. The difference from Embodiment 1 is that in step 2, a tubular furnace is used for heating. The heating is carried out under nitrogen protection at a rate of 5°C / min to 1300°C, and the temperature is kept for 5 hours, followed by natural cooling.

[0066] Test example

[0067] The specific surface area and pore size distribution of the regenerated graphite obtained in the embodiment and the comparative example were tested using nitrogen adsorption and desorption isotherms and pore size distribution curves, respectively. The assembled battery was placed in a constant temperature box at 25°C for 12 hours and connected to a blue power test system. The test was performed according to the procedure, and the charge and discharge curve interval was set to 2.0-0.0005V, and constant current charge and discharge were performed at different current rates.

[0068] The test results are shown in Table 1 below.

[0069] Table 1. Comparison of structural properties and electrochemical properties of different recycled graphites

[0070] It can be seen from the experimental data in Table 1 that the normalized regeneration method for the performance of negative electrode graphite of multi-source retired lithium-ion batteries of the present invention can recycle multi-source negative electrode graphite, and a good repair effect can be achieved in a short time of heat preservation. The performance of the regenerated graphite (FG) obtained in Example 1 is compared with that of the initial raw material graphite scraps SG, the negative electrode graphite material DG obtained by disassembling retired power batteries, and the graphite HG in the hydrometallurgical leaching slag of crushed black powder of retired power batteries. Figure 2-4 As shown, the regenerated graphite (FG) obtained by the method of the present invention has significantly improved rate performance, initial charge and discharge performance and cycle performance under 0.1C current conditions. The gram capacity of the obtained regenerated graphite under 0.1C current conditions is greater than 330mAh / g, and the capacity is maintained at more than 90% after 100 cycles at 1C current. The gram capacity of the regenerated graphite obtained under the conditions of Examples 1, 4, 5, 7 and 8 under 0.1C current conditions is greater than 345mAh / g, and the capacity is maintained at more than 99% after 500 cycles at 1C current.

[0071] It can be seen from the results of Example 1 and Comparative Examples 2-3 that, compared with the repair methods of microwave treatment and high-temperature sulfuric acid roasting, the method of the present invention can significantly improve the repair effect and efficiency, and achieve rapid repair of retired negative electrode graphite materials. It can be seen from the results of Example 1 and Comparative Example 3 that, compared with the traditional tubular furnace heating, the present invention adopts flash discharge heating, and the energy utilization effect is higher. The traditional tubular furnace heating energy utilization rate is extremely low, and the surface organic matter (such as PVDF binder) and residual SEI can be gradually removed as the temperature rises. However, the deep graphite damaged structure is poorly repaired due to insufficient energy concentration.

[0072] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for normalizing the performance of negative electrode graphite of multi-source retired lithium-ion batteries, characterized in that: The steps include: Step 1: Mixing multiple sources of retired lithium-ion battery negative electrode graphite raw materials in a certain proportion to obtain multiple source mixed failed graphite raw materials; Step 2: Add the multi-source mixed spent graphite raw material obtained in step 1 into a graphite device, and then perform flash discharge treatment to obtain regenerated graphite.

2. The method for normalizing the performance of negative electrode graphite of multi-source retired lithium-ion batteries according to claim 1, characterized in that: The multi-source retired lithium-ion battery negative electrode graphite raw materials include graphite scraps produced in the production process of negative electrode materials, negative electrode graphite materials obtained by disassembling retired power batteries, and graphite in leached slag obtained by hydrometallurgy of crushed black powder of retired power batteries; Preferably, in the multi-source retired lithium-ion battery negative electrode graphite raw materials, the weight ratio of graphite scraps generated in the production process of negative electrode materials, negative electrode graphite materials obtained by disassembling retired power batteries, and leached slag obtained by hydrometallurgy of crushed black powder of retired power batteries is (1-5): (1-2): (1-3).

3. The method for normalizing the performance of negative electrode graphite of multi-source retired lithium-ion batteries according to claim 1, characterized in that: In the step 2, the flash discharge treatment is to place a graphite device containing multi-source mixed failed graphite raw materials in a flash discharge device, raise the temperature to the reaction temperature at a certain heating rate, keep the temperature for a period of time and then cool it to obtain regenerated graphite.

4. The method for normalizing the performance of negative electrode graphite of multi-source retired lithium-ion batteries according to claim 3, characterized in that: The reaction temperature is 2800-3200° C., and the insulation time is 0.1s-10s.

5. The method for normalizing the performance of negative electrode graphite of multi-source retired lithium-ion batteries according to claim 3, characterized in that: The heating rate is 0.01°C / s to 3000°C / s, preferably 1°C / s to 3000°C / s; and / or, the discharge current of the flash discharge treatment is 5 to 15A, and the discharge voltage is 150 to 200V; and / or, the cooling includes natural air drying cooling or cooling at a cooling rate of 0.01°C / s to 3000°C / s, preferably cooling at a cooling rate of 0.01°C / s to 3000°C / s.

6. The method for normalizing the performance of negative electrode graphite of multi-source retired lithium-ion batteries according to claim 1, characterized in that: The flash discharge treatment is performed in a specific gas atmosphere, wherein the specific gas includes one or more of nitrogen, argon, oxygen and air, preferably one or two of nitrogen and argon.

7. The method for normalizing the performance of negative electrode graphite of multi-source retired lithium-ion batteries according to claim 1, characterized in that: The graphite device is one or more of a graphite boat, a graphite tube and graphite carbon paper.

8. The method for normalizing the performance of negative electrode graphite of multi-source retired lithium-ion batteries according to claim 1, characterized in that: The flash discharge treatment in step 2 is performed to obtain a reaction product, and the obtained reaction product is washed and then vacuum dried to obtain regenerated graphite; Preferably, the washing solution used in the washing is a mixture of one or more of hydrochloric acid, sulfuric acid, phosphoric acid and water; more preferably, the concentration of the washing solution is 0.01 mol / L to 8 mol / L.

9. The method for normalizing the performance of negative electrode graphite of multi-source retired lithium-ion batteries according to claim 1, characterized in that: In the step 1, multiple sources of retired lithium-ion battery negative electrode graphite raw materials are mixed in a certain proportion and then sieved through a 50-200 mesh sieve to obtain multiple source mixed failed graphite raw materials.

10. The method for normalizing the performance of negative electrode graphite of multi-source retired lithium-ion batteries according to claim 1, characterized in that: The regenerated graphite has a gram capacity of 300 mAh / g to 400 mAh / g under 0.1C current conditions and a specific surface area of ​​2 m 2 / g~20m 2 / g, pore volume 10m 3 / g~100m 3 / g.

Citation Information

Patent Citations

  • Recycling method of decommissioned lithium ion battery negative electrode graphite

    CN111924836A

  • Method for synergistically regenerating positive and negative electrode materials of lithium ion battery, materials and application

    CN114447465A

  • Modification method of negative electrode material of retired lithium ion battery

    CN114709506A

  • Method for recycling and regenerating graphite negative electrode material of waste lithium battery

    CN117185289A

  • Graphite material purification process

    WO2024003761A1

Cited By

  • Porous graphite material prepared by regenerating retired graphite electrode as well as preparation method and application of porous graphite material

    CN122102114A